Effectiveness of small-diameter timber piles to enhance the bearing capacity of micropiled foundation in soft clays - Yusti Yudiawati; Ari Surya Abdi; Muhammad Dwiyanto Agung Prakasa (Results in Engineering)
Small-diameter natural timbers like gelam and ironwood have been widely used in constructing micropile foundations, particularly in undrained soft clay. However, the design approaches and analytical methods for micropile foundations using gelam and ironwood remain highly empirical, with limited studies investigating their load transfer mechanism. Their application often depends on empirical knowledge and field experience. In this study, a series of three-dimensional finite element analyses was conducted to simulate the actual arrangement and behavior of micropile systems, focusing on two foundation types utilizing gelam wood micropiles: ironwood with gelam wood micropiles (IMP) and concrete footing with gelam wood micropiles (FMP). The numerical results are initially validated through the field test data. According to the numerical results, for IMP models, load transfer begins with ironwood side friction, followed by tip resistance and additional base support from horizontal Gelam wood, while in FMP models, Gelam wood friction and tip resistance mobilize first, with the footing starting to contribute thereafter, enhancing bearing capacity and reducing settlement. Furthermore, the use of micropiles could effectively increase the bearing capacity to more than twice that of without micropiles for both IMP and FMP models. Additionally, for configurations with four micropiles, a spacing-to-diameter ratio of six is optimal for maximizing bearing capacity and minimizing settlement.